Echolocation in Bats: A Fascinating Array - Mukherjee, Saptabarna; Mohapatra, Animesh K. (SCHOOL SCIENCE, 2016)
The paper discusses the process of use of sound to distinguish the objects present in our environment known as echolocation. It can also be defined as the process of visualizing with the aid of sound, which is remarkably utilized by those organisms lacking efficient vision power. It is very astonishing that the diverse range of vertebrates uses sound to acquire their food and shelter supplemented with the aim to escape from their enemies to ensure the continuity of their race. These include the bats (Chiropterans), dolphins, whales (Odontocetes), birds, shrews, swift lets, porpoises, etc.